2018
DOI: 10.1111/bjop.12358
|View full text |Cite
|
Sign up to set email alerts
|

Acute stress responses after indirect exposure to the MH17 airplane crash

Abstract: People can experience disasters vicariously (indirectly) via conversation, social media, radio, and television, even when not directly involved in a disaster. This study examined whether vicarious exposure to the MH17‐airplane crash in Ukraine, with 196 Dutch victims, elicited affective and somatic responses in Dutch adults about 2,600 km away, who happened to participate in an ongoing diary study. Participants (n = 141) filled out a diary three times a day for 30 days on their smartphones. Within‐person chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 102 publications
(163 reference statements)
4
17
0
Order By: Relevance
“…Older participants (ages between 35 and 60) had a higher QoL than younger participants (age ≤ 35). Our conclusion is consistent with an air crash observation, which found that older individuals reported a smaller increase in negative effects caused by the MH17 crash than younger participants ( Jeronimus et al, 2019 ). One possible explanation might be that older medical staff have more experience, professional skills, sophisticated coping strategies to deal with risks and crises, and pay less attention to negative information ( Piotrkowska et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Older participants (ages between 35 and 60) had a higher QoL than younger participants (age ≤ 35). Our conclusion is consistent with an air crash observation, which found that older individuals reported a smaller increase in negative effects caused by the MH17 crash than younger participants ( Jeronimus et al, 2019 ). One possible explanation might be that older medical staff have more experience, professional skills, sophisticated coping strategies to deal with risks and crises, and pay less attention to negative information ( Piotrkowska et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, several recent studies have proved that regular physical activity can lead to positive behavioral changes, strengthen the immune system, and reduce negative psychological impacts ( Alsalhe et al, 2020 ; Jiménez-Pavón et al, 2020 ; Slimani et al, 2020 ). Although theoretical and empirical evidence suggested that there might be a strong link between acute stress and general health outcomes, acute post-traumatic stress responses have not been well studied in health care workers ( Holman et al, 2014 ; Jeronimus et al, 2019 ). It is imperative to assess the acute stress responses after a traumatic event to predict long-term health consequences ( Dai et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…These results were also consistent with the previous COVID-19 studies of the psychological impacts of disasters [29,31]. Exactly why this is the case remains somewhat unclear: Perhaps older persons direct more cognitive effort to maintaining positive emotions and avoiding negative ones("positive effects") [32]. Conversely, maybe younger residents face greater social, emotional, and/or economic responsibilities toward their families' health and protection.…”
Section: Discussionsupporting
confidence: 89%
“…It has been reported that traditional extended family systems, such as those in South Asia, can contribute to healthier mental states among older people as compared to those living in smaller nuclear family systems [ 43 ]. Positive attitudes stemming from a lack of information about COVID-19 could also be another factor for better mental health of older people [ 44 ]. As compared to older people, younger people rely more on social media and the internet that have helped to spread negative information on the pandemic [ 14 , 27 ].…”
Section: Discussionmentioning
confidence: 99%